2007
DOI: 10.1063/1.2767979
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive thickness measurement of biological layers at the nanoscale by simultaneous topography and capacitance imaging

Abstract: Nanoscale capacitance images of purple membrane layers are obtained simultaneously to topography in a nondestructive manner by operating alternating current sensing atomic force microscopy in jumping mode. Capacitance images show excellent agreement with theoretical modeling and prove to be a noninvasive method for measuring the thickness of purple membrane layers beyond the single monolayer limit with nanoscale lateral spatial resolution. With the ability of spatially resolving the capacitance while preservin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…10 we demonstrated that simultaneous capacitance and topographic profiling measurements on a micro/ nanopatterned dielectric film allow one estimating in a very quantitatively way the thickness of the film at the nanoscale with high vertical resolution.…”
Section: B Capacitance Profile Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…10 we demonstrated that simultaneous capacitance and topographic profiling measurements on a micro/ nanopatterned dielectric film allow one estimating in a very quantitatively way the thickness of the film at the nanoscale with high vertical resolution.…”
Section: B Capacitance Profile Measurementmentioning
confidence: 99%
“…The remaining contributions conform the stray capacitance contribution that can be subtracted from the experiments following an appropriate calibration procedure as previously reported. 1,6,10 In order to arrive at an analytical expression for the apex capacitance in the presence of a thin dielectric film, we will restrict ourselves to the model system depicted in Fig. 1͑b͒.…”
Section: A Theoretical Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Unfortunately, the effect of the electrostatic field under these restrictions has not been studied in detail since previous theoretical works focused on dielectric thin films over metallic substrates. 15,16 In this article, we combine numerical methods and artificial neural networks 17 (ANNs) to simulate the electrostatic interaction between an EFM tip and a thin film. Using the electrostatic force as input patterns to the ANN, we establish that the thin film sample can be replaced by a simple semiinfinite sample characterized by an effective dielectric constant.…”
mentioning
confidence: 99%
“…12 EFM is currently used to determine the static dielectric constants of thin films of a few nanometers thickness directly deposited on a metallic electrode. The dielectric constant can be determined by comparison of the experimental results with simple analytical expressions 13,14,15 . For metallic samples, the tip-sample interaction is very well understood and the force, as well as the force gradient, can be determined by using a simple analytical model.…”
Section: Introductionmentioning
confidence: 99%